Spatial and temporal trends of climate change in the Kandy district of Sri Lanka based on precipitation and temperature - Nagamuthu, Piratheeparajah; Sivakumar, Dhanushika (Penerbit Universiti Kebangsaan Malaysia, 2024)
Climate change stands as one of the most paramount environmental predicaments in the present world. Recent years have seen an escalation of climate change into a truly global issue. In light of this, our study aims to identify the spatiotemporal patterns of climate change, specifically with regards to temperature and precipitation, in Kandy district throughout the period spanning 1992 to 2022. By critically appraising the contemporaneous situation, the study seeks to provide recommendations aimed at curbing the impact of climate change. Another relevant study was conducted, focusing on secondary data, mainly climatological observations. The current investigation utilised the Sri Lanka Metrology Department's spatial trend data administered through the IDW method on Arc GIS 10.4. On the other hand, the temporal trend data were evaluated using the Mann Kendall trend and Sen's slope estimator methods through MiniTab16. The outcomes of this research have been presented through the processing of imagery and tabulating data, which have been subjected to rigorous statistical analyses. As far as the district of Kandy is concerned, the variability of rainfall and temperature across different areas is undeniable. The district's average temperature lies at 0.516°C, with the average high temperature being 0.606°C and the average low temperature being 0.408°C. Rainfall in Kandy district has intensified to 2604 mm, with the Nawalapitiya rainfall observation station showing an increase in trend to 2763 mm, while the Duck wary Estate rainfall observation station displaying a decreased trend to 996.927 mm. In the monsoon season, the south-westerly monsoon season promotes increased rainfall up to 1905 mm, while the north-easterly monsoon season loses its previously known influence on seasonal rainfall, resulting in only 80.34 mm. Meanwhile, the temperature in Kandy District has intensified by 1.98°C. Given the observed disparities in climate, location, and time, there are numerous challenges in planning for development. Effective mitigation measures are paramount for the amelioration of climate change.